Religion and Nationalism in Shaping the Fiqh of Armed Jihad: A Lesson to the Indonesian National Counterterrorism Policy - Munajat, Munajat (AHKAM : Jurnal Ilmu Syariah, 2022)
Understanding the formulation of the fiqh of jihad is a key success in countering violent  Islamist  extremism  and  terrorism. Two salient factors that often come up in the academic  discussion  of  the  making  of  violent jihad are nationalism and religion. The present study investigates these two crucial  related  factors  in  the  two  prominent  cases  of  armed  jihad  in  Iran (1980-1988) and Palestina (1990-2010); and, then, how they may provide a lesson to the counterterrorism policy in Indonesia. The study uses secondary data  to  investigate  the  making  of  violent  jihad  of  Iran  and  the  Palestinian Hamas. While in the case of Indonesian policy, this article uses a government report  on counterterrorism  and  interviews  with  the  state  counterterrorism authorities. This study shows that the interactions of two ideologies (religion and nationalism) together create a sustained and powerful force of a violent jihad by the Iranians during the Iraq-Iran War and Palestinian Hamas against Israel to achieve their political goals. In contrast to this practice, Indonesia has applied nationalism in counterterrorism policies as a strategy to deradicalize violent ideology with religious motives. This article shows that counterterrorism policies need to put more emphasis on the meaning of non-violent jihad.Keywords: religion; nationalism; jihad; counterterrorism AbstrakMemahami fikih jihad merupakan kunci keberhasilan dalam melawan ekstrimisme  dan  terorisme.  Dua  faktor  yang  sering  muncul  dalam  diskusi akademis tentang pembentukkan wacana jihad kekerasan adalah nasionalisme dan  agama.  Studi  ini  menyelidiki  dua  faktor  penting  dalam  kasus  jihad bersenjata  di  Iran  (1980-1988)  dan  Palestina  (1990-2010);  dan  bagaimana kasus ini menjadi pertimbangan dalam kebijakan kontraterorisme di Indonesia. Studi ini menggunakan data sekunder untuk menyelidiki pembentukkan jihad kekerasan di Iran dan Hamas Palestina. Pada konteks Indonesia, penelitian ini menggunakan  laporan  pemerintah  tentang  kontraterorisme  dan  wawancara dengan  otoritas  terkait.  Hasil  penelitian  menunjukkan  bahwa  interaksi  dua ideologi (agama dan nasionalisme) secara bersama-sama menciptakan kekuatan jihad kekerasan yang signifikan dan berkelanjutan di Iran selama Perang Irak- Iran  dan  Hamas  Palestina  melawan  Israel  dalam  mencapai  tujuan  politik. Berbeda dengan praktik tersebut, Indonesia menggunakan nasionalisme dalam kebijakan kontraterorisme sebagai strategi melawan ideologi kekerasan bermotif agama. Artikel ini menunjukkan bahwa kebijakan kontraterorisme perlu lebih menekankan pada pemaknaan jihad tanpa kekerasan.Kata Kunci: agama; nasionalisme; jihad; penanggulangan terorisme